2015
DOI: 10.1088/0264-9381/32/15/155008
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Hartle's model using perturbed matching theory to second order: amending the change in mass

Abstract: Hartle's model describes the equilibrium configuration of a rotating isolated compact body in perturbation theory up to second order in General Relativity. The interior of the body is a perfect fluid with a barotropic equation of state, no convective motions and rigid rotation. That interior is matched across its surface to an asymptotically flat vacuum exterior. Perturbations are taken to second order around a static and spherically symmetric background configuration. Apart from the explicit assumptions, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(69 citation statements)
references
References 30 publications
(238 reference statements)
3
66
0
Order By: Relevance
“…The complementary functions here satisfy the homogeneous forms of equations (3.74) and (3.75) 85) which have the following behaviors near the origin…”
Section: Structure Equations For the Schwarzschild Starmentioning
confidence: 98%
See 1 more Smart Citation
“…The complementary functions here satisfy the homogeneous forms of equations (3.74) and (3.75) 85) which have the following behaviors near the origin…”
Section: Structure Equations For the Schwarzschild Starmentioning
confidence: 98%
“…Recently Reina & Vera [84,85] revisited Hartle's framework within the context of the modern theory of perturbed matchings [56]. They found that the perturbative functions at first and second order are continuous across the boundary of the configuration except when the energy density is discontinuous there.…”
Section: Amended Change Of Massmentioning
confidence: 99%
“…Assumption (iii) has significant implications on the properties of the stellar models. As shown by Reina & Vera (2015) using the framework of Mars (2005), a relevant perturbative function presents a discontinuity proportional to the (background) energy density in the stellar surface. This function enters the computation of the mass of the star at second order δ M and, therefore, the original expression for the total mass of the rotating star given in Hartle (1967) has to be amended.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, one assumption taken explicitly in [7] regarding the causal character of the hypersurfaces, as they are assumed to be timelike or spacelike everywhere. This method has been applied to linear order to obtain uniqueness results for the Einstein-Strauss model [9] and to second order to revisit the problem of slowly rotating stars [14].…”
Section: Introductionmentioning
confidence: 99%